A Confirmatory Factor Analysis of the Spanish Language Version of the Attitudes Toward Lesbians and Gay Men (ATLG) Measure - Barrientos Delgado, Jaime Eduardo; Universidad Catolica del Norte (2011)
This paper intends to validate the Attitudes toward Lesbians and Gay Men Scale (Herek, 1988). The starting point is the five dimensions reported in previous studies (Cardenas & Barrientos, 2008). No research has confirmed the hypothesized ATLG factor structure with a Spanish-language sample. This study tested three factor structures, results indicating that the two factor second-order model provides the best description of ATLG items. Additionally, psychometric properties were examined using a sample of 518 college students. ATLG proved reliable (α = 0.93) and valid for Chilean population.